Phototherapy Training to Improve Students' Physical Literacy and Psychological Support through Guidance and Counseling Services (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The psychological well-being of primary and secondary school students is a crucial factor influencing their learning success. However, many teachers still face challenges in understanding and responding to students’ emotional expressions. Phototherapy, a creative approach using visual media, has the potential to enhance physical literacy while supporting counseling practices in schools. The phototherapy training program was conducted through interactive workshops involving primary and secondary school teachers. The methods included participatory lectures, practical simulations, group discussions, and guided reflections. Data were collected through observation, interviews, and teachers’ reflective notes regarding their experiences and application of phototherapy strategies in classroom and counseling contexts. The training improved teachers’ knowledge and skills in using photographic media as a tool to recognize, explore, and manage students’ emotional expressions. Teachers also demonstrated increased readiness to implement phototherapy approaches both in daily classroom activities and in counseling sessions. Phototherapy training proved to be relevant and beneficial for teachers, expanding their understanding of creative strategies to support students while strengthening their practical skills in education and counseling. This finding highlights the significance of integrating creative expression-based approaches into educational practice, offering an innovative model to promote students’ psychological well-being in a sustainable way.